ANALISIS PROFITABILITAS USAHA RUMAH TANGGA NELAYAN PERIKANAN (RTNP) TANGKAP TUNA DI KABUPATEN MALUKU TENGAH - Steven Siaila (Soso-Q : Jurnal Manajemen, 2017)
This paper aims to assess the prospects for the development of tuna fishing RTNP in Central Maluku regency through the analysis of business profitability. Variables used in this analysis is the variable Return on Assets (ROA) as dependent variable and independent variables are the investment, the experience of fishing and fishing fees.The sampling method used is a simple method of sample Ransom (Simple Random Sample Method) by using regression analysis utilize computer software as a data processor.It turned out that the investment is positive but not significant effect on profitability business RTNP tuna catch, while the fishing experience of a positive effect on profitability of the business expenses otherwise negatively affect the profitability of fishing effort RTNP Tuna fishing in Central Maluku regency. This means that a major requirement for business development RTNP tuna catch is that apparently control the cost of fishing has a negative effect on profitability. Keywords: fishing activity, Profitability